PERMASALAHAN SOSIAL ANAK HIPERAKTIF: Social Problems of Hyperactive Children - Amseke, Fredericksen Victoranto; Bien, Alya (Yayasan Al-Amin Qalbu, 2025)
Hyperactive children often face challenges in social interactions due to behavior characterized by excessive movement, difficulty maintaining attention, and impulsivity, which is often associated with Attention Deficit Hyperactivity Disorder (ADHD). The aim of this research is to explore the social behavior of hyperactive children and its treatment in an educational context and to understand how hyperactive behavior affects children's social interactions. This research method is a qualitative descriptive research method. The data collection techniques used were observation, interviews and documentation. The subjects in this research were one parent who had a hyperactive child, one teacher, and the principal at PAUD Margherita Ricci Curbastro Osiloa. Research results show that children with hyperactive behavior often experience difficulties in social interaction. Movement that is difficult to keep still is one of the characteristics that hinders their ability to interact with their peers and the surrounding environment. Teachers are advised to create an inclusive classroom environment because every child feels welcome with flexible management strategies according to the child's needs. Parents are advised to provide consistent emotional support and take time to talk about their children's feelings so they feel heard and cared for. With close collaboration between teachers and parents, it is hoped that hyperactive children can better face the social challenges they experience and achieve optimal development in social and emotional aspects